Strategi Pembelajaran Produk Kreatif dan Kewirausahaan Bidang Busana Di Sekolah Menengah Kejuruan - Widarti, Wahyu Tri; Siti Mariah; Setyaningsih, Rina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to describe and analyze learning strategies in the subjects of creative products and entrepreneurship in the fashion sector which include: 1) Learning planning, 2) Learning implementation and 3) Evaluation of learning outcomes. This study used the qualitative method with the research subjects of the head of the department, supervisory teachers and class XII fashion design students at SMK Negeri 4 Yogyakarta. Data collection methods include: interviews, observation, and documentation. The validity of the data is done by triangulation techniques, triangulation of sources and time. Data analysis techniques include: data collection, data reduction, data presentation, conclusion drawing and verification. The results showed that: 1) Planning for learning creative and entrepreneurial products available in the form of lesson plans, syllabi, learning media and teaching materials. 2) The implementation of creative and entrepreneurial product learning includes several things, namely: at the beginning of learning the teacher gives lighter questions; The learning model used is project-based learning with a cooperative learning strategy; the learning method is to explain the material with lecture methods, groups and peer tutors; learning media using PowerPoint and handouts; In the closing activity, the teacher conveyed conclusions related to the material that had been explained. 3) Evaluation of creative and entrepreneurial product learning outcomes is carried out throughout learning at each stage of the product manufacturing process and the form of evaluation assessment includes cognitive, affective and psychomotor assessment